MEANS OF ENHANCING FIGURATIVE THINKING IN UZBEK AND ENGLISH LANGUAGES (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This article explores linguistic and stylistic tools that contribute to the development of figurative thinking in Uzbek and English languages. It analyzes the role of metaphor, metonymy, epithet, phraseological units, and other expressive means in expanding cognitive scope and enhancing aesthetic and logical reasoning. The influence of structural and cultural differences between the two languages on figurative expression is also discussed. The findings have practical value for both language teaching and translation studies.